An arrival time picker for microseismic rock fracturing waveforms and its quality control for automatic localization in tunnels. (July 2021) - Zhang, Wei; Feng, Xia-Ting; Bi, Xin; Yao, Zhi-Bin; Xiao, Ya-Xun; Hu, Lei; Niu, Wen-Jing; Feng, Guang-Liang
Abstract: The accurate picking of waveform arrival times is fundamental to microseismic (MS) monitoring technology and is related to the location accuracy of MS sources. An urgent requirement is an automatic and accurate method for picking up the MS waveform arrival times to realize automatic MS monitoring. In this work, a new arrival time picker has been designed to pick up the P- and S-wave arrival times of MS waveform automatically in tunnels. A control model for the arrival time quality of the S-wave ( ATQS ) is proposed to automatically identify waveforms with high ATQS values, and the S-wave arrival time of the waveforms is subsequently used in MS source location, to improve the automatic location accuracy. Many rock fracturing waveforms are used to construct a sample database. The experimental and engineering applications show that the P- and S-wave arrival time accuracies are 94.39% and 91.59%, respectively. The automatic location error of a rockburst event is reduced from 42.2 m to 15.3 m. The arrival time picker proposed in this paper demonstrates high accuracy, which ensures the automatic location accuracy of MS sources and lays a foundation for the realization of automatic MS monitoring.